التنوع اللغوي أسبابه و شروطه في اللغة العربية في نظر القدماء و المحدثين من اللغويين العرب: Linguistic diversity, its causes and conditions in the Arabic language, in the view of ancient and modern Arabic linguists - حركاتي, ميلود (Maalim, 2022)
This research deals with the linguistic diversity aspects in the classical Algerian Arabic which corresponds to the linguistic diversity in the classical Oriental Arabic since ancient times, and it is called for the linguists (The Arabized and the foreign words) or (the modernists language borrowing). This research also aims to shed light on the Arab and the foreign words in the eyes of the ancients and the modernists, and its presence in the Holy Quran and the conditions of Arabization, with an indication of the reasons for the existence of this linguistic diversity that goes back to the relations between peoples that were bordering the Arabs from a long time ago. But are these extraneous and Arabized expressions still entering to the Arabic language, or have they stopped? This is the problem that this research will try to answer.